1991
DOI: 10.1530/jrf.0.0930609
|View full text |Cite
|
Sign up to set email alerts
|

Immunoreactive cytochrome P-45017  in rat and guineapig gonads, adrenal glands and brain

Abstract: The cytochrome P-450(17 alpha)-hydroxylase, 17----20 lyase (P-450(17 alpha)) is the key enzyme responsible for the biosynthesis of androgens in steroidogenic organs. Its cellular localization has been examined with an immunohistochemical technique. In immature rat ovary, P-450(17 alpha) was first detected in sparse interstitial cells on postnatal Day 8. The number of immunoreactive interstitial cells increased thereafter and the intensity of P-450(17 alpha) staining in these cells was highest at 3 weeks of age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
68
1
2

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(75 citation statements)
references
References 22 publications
4
68
1
2
Order By: Relevance
“…Le Goascogne et al (1991) reported immunoreactive P450C17 in rat gonads but not in the adrenals, thus confirming the absence of expression of this cytochrome in this species. In the mouse, Keeney et al (1995) reported clusters of fetal adrenal cells that hybridize specifically with murine P450C17 cRNA.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Le Goascogne et al (1991) reported immunoreactive P450C17 in rat gonads but not in the adrenals, thus confirming the absence of expression of this cytochrome in this species. In the mouse, Keeney et al (1995) reported clusters of fetal adrenal cells that hybridize specifically with murine P450C17 cRNA.…”
Section: Discussionmentioning
confidence: 66%
“…1996). The results obtained in the guinea pig and the pig demonstrated that P450C17 was present only in the zonae fasciculatae (ZF) and reticularis, with intense immunoreactivity in cells of the outer fasciculata zone and decreasing intensity towards the reticularis cells (Shinzawa et al 1988;Le Goascogne et al 1991;Colby et al 1993). In the adrenal cortex of the rat, however, no immunoreactivity could be detected, which is in accordance with the fact that their adrenal glands do not express P450C17 (Van Weerden et al 1992).…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Klju~ne re~i: programiranje, fetalni razvoj, HPA osovina, deksametazon, betametazon, antenatalna terapija pus luteum and in the fetal gonads (10). Thus, the placenta and the fetal adrenals make a unique fetoplacental functional unit that controls and adjusts HPA axis functioning during in utero development.…”
Section: Pregnancy and The Hpa Axismentioning
confidence: 99%
“…Blood levels of dehydroepiandrosterone (DHEA) in humans decline significantly with age and parallels cognitive decline (Orentreich et al, 1992). Rodents, in contrast, have very little DHEA in brain because of the lack (or undetectable levels) of cyp17␣ (17␣-hydroxylase) that catalyzes the conversion of pregnenolone (PREG) to DHEA in rat and mouse adrenal cortex (Le Goascogne et al, 1991;Mellon and Deschepper, 1993). However, high levels of PREG, the neurosteroid precursor of DHEA, can be detected in the hippocampus of young rats, whereas aged rats have lower levels, which correlate with cognitive deficits .…”
Section: Introductionmentioning
confidence: 99%